Coupling thin layer chromatography with mass spectrometry for detection and identification of sertraline and its metabolite in the urine - S. B. Baiurka; S. A. Karpushyna; N. M. Kosmina; L. V. Krichkovskaya; I. Ye. Bylov; O. O. Altukhov (Zaporozhye State Medical University, 2024)
The aim of the study was to detect sertraline and its metabolites in urine under standardized thin layer chromatography (TLC) screening conditions and identify the metabolites using the mass spectrometry method. Materials and methods. Urine samples, collected within 30 hours in portions of 20-50 mL, commenced from the seventh hour after the administration of a single therapeutic dose of the drug. The sample preparation process involved dilute acid hydrolysis, followed by the extraction of the native compound and metabolites with chloroform at a pH of 8-9. Thin layer chromatography studies of the extracts were conducted using four unified TLC systems recommended by The International Association of Forensic Toxicologists for general drug screening. Chromatograms were subjected to color reactions with a variety of chromogenic reagents. For the analysis of eluates from chromatograms, a Varian 1200 L mass spectrometer (Netherlands) equipped with a dual quadrupole mass analyzer was employed. Identification was performed through direct sample introduction into the ion chamber, electron-impact ionization (70 eV), and full ion scanning mode. Results. The spot of the native drug on the chromatogram was identified by the Rf, value. Metabolite of sertraline was identified as N-desmethyltrihydroxysertraline by the molecular ion peak in the mass spectrum. Conclusions. The study demonstrated the ability of TLC to detect sertraline and its metabolite, N-desmethyltrihydroxysertraline, in urine after the administration of a single therapeutic dose of the drug. The chromatographic mobility of the native compound and N-desmethyltrihydroxysertraline in the unified TLC screening systems, along with the results of their visualization using chromogenic reagents for toxicological drug screening, was determined. Furthermore, the potential of coupling TLC with mass spectrometry for the separation, detection, and confirmatory identification of sertraline and its metabolic products in urine was established.